Effects of graded hypoxia on the time course of neuromuscular adjustments during maximal, intermittent leg extensions - Christian, R.; Girard, O.; Billaut, F.; Bishop, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Fatigue during high-intensity intermittent exercise has been shown to occur as a result of both neural and muscular factors. However, due to neuromuscular assessments usually being restricted to pre- and post-exercise only, the time course, interplay and regulation of neural and muscular adjustments during such exercise is not well understood. Aim: To investigate the effect of hypoxia severity on the time course of neuromuscular adjustments during maximal intermittent leg extensions. Methods: Twelve trained, team-sport athletes (age: 28±6 y; stature: 180±6 cm; mass: 82±6 kg) performed 4 bouts of intermittent exercise (separated by 100 s of rest); each bout included 6 sets (separated by 15 s of rest) of 5 maximal, continuous, isokinetic leg extensions at 300 °/s. There were 3 conditions: normoxia (simulated altitude/fraction of inspired oxygen = 0 m/0.21%), moderate (3000 m/0.14%) and severe hypoxia (5400 m/0.10%) which were performed in a randomised counterbalanced order. Arterial oxygen saturation (Sp02), heart rate (HR) and rating of perceived exertion (RPE) were recorded 10 s after each contraction set. Neuromuscular assessments including voluntary and evoked contractions of the knee extensors using both peripheral motor nerve and transcranial magnetic stimulations were completed prior to exercise, in-between each set, immediately, 5, 15 and 30 minutes post-exercise. Results: Preliminary data (n=7) show that average peak power output during the first set was similar among the three conditions (180.9 ± 35.7 N.m-1, all conditions compounded; p=1.00). Irrespectively of the conditions average peak power output decreased (p<0.05) from the first to the fourth exercise bout (percentage decrement score: -4.6%, -6.0% and -8.1% in normoxia, moderate and severe hypoxia, respectively), while HR and RPE (+9% and +23%, respectively; all conditions compounded; both p<0.01) increased. RPE values during the fourth bout (+5.0% and +4.2%, respectively) were higher in severe hypoxia than in normoxia or moderate hypoxia. Compared to baseline, Sp02 remained constant in normoxia (98%) but decreased in moderate and severe hypoxia (91% and 80%, respectively; both p<0.05) after 10 min wash-in. Sp02 did not further decrease throughout exercise in any condition. Conclusion: During maximal, intermittent leg extensions, preliminary evidence suggests that larger performance decrements occur with increases in hypoxia severity. With our complete sample size, additional data will help to shed more light on the time course of neuromuscular adjustments that may eventually explain the larger performance decrement observed with severe hypoxia.